ANALISIS HAMBATAN PROSES PEMBELAJARAN BIOLOGI DALAM PELAKSANAAN KURIKULUM 2013 BAGI GURU KELAS X SMA/SEDERAJAT DI KECAMATAN RAMBAH SAMO - -, PRAMONO (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This research is a descriptive study. The method used to collect data were questionnaires, documentation and interviews. This research has been carried out in July 2015 at the high school / equivalent District of Rambah Samo with samples in this study were 5 teachers of biology. Learning process biological barriers in the implementation of the curriculum in 2013 are: (1) The training material curriculum in 2013 is not in accordance with the needs of school learning, the criteria are less good (50%); (2) The scientific approach presented in the training curriculum of 2013 is less clear in the running concept with unfavorable criteria (50%); (3) Sample authentic assessment presented in the training are not clear with the criteria of unfavorable (50%); (4) The concept of integrated learning can not be conveyed properly in training with the criteria of unfavorable (50%); (5) Method of hard training followed by criteria fairly well (55%) and (6) Method of training less fun with the criteria fairly well (55%).